Non-universal critical properties of a symmetrical binary fluid mixture - Patsahan, O.V.; Melnyk, R.S.; Kozlovskii, M.P. (Condensed Matter Physics, 2001)
We study non-universal critical properties of a symmetrical mixture using the recently proposed approach and the method of layer-by-layer integration of a partition function. Both the gas-liquid critical point properties (temperature and density) and the fluid-fluid demixing temperature of a symmetrical hard-sphere square-well mixture are calculated depending on its microscopic parameters: the parameter r measuring the strength of interactions between the particles of dissimilar and similar species and the parameter λ measuring the width of the potential well.